Duration and dose of antiepileptic drugs and serum calcium levels in children - Arinta Atmasari; Masayu Rita Dewi; Aditiawati Aditiawati; Masagus Irsan Saleh (Indonesian Pediatric Society, 2017)
Background Antiepileptic drugs (AEDs) may affect calcium metabolism through several mechanisms. Much evidence has confirmed that carbamazepine and valproic acid, as the most widely used AEDs in epileptic children, leads to decreased serum calcium levels. This effect was suggested to be time and dose dependent. However, correlations between AEDs and calcium levels in Indonesian epileptic children have not been well studied.Objective To investigate possible correlations between total calcium levels and durations of therapy as well as doses of carbamazepine and valproic acid.Methods This analytical, cross-sectional study was performed from March to May 2015 in the Neuropediatric Outpatient Ward of Mohammad Hoesin Hospital, Palembang, South Sumatera. A total of 60 epileptic children taking carbamazepine and or valproic acid monotherapy were included and grouped accordingly. A single blood test was done for every participant to measure total serum calcium level. Correlation between daily dose or duration of AED with calcium level was assess using the Spearman-rho test.Results The mean total serum calcium levels in the carbamazepine and valproic acid groups were 9.48 (SD 0.83) mg/dL and 9.58 (SD 0.63) mg/dL, respectively. There was a statistically significant moderate correlation between the duration of carbamazepine therapy and total calcium level (r = 0.36; P=0.001). The cut-off point for duration of therapy was 23 months. There were no significant correlations between total calcium level and mean daily carbamazepine dose, nor between total calcium level and duration and dose of valproic acid therapy.Conclusion Longer duration of carbamazepine therapy is associated with low total serum calcium level, but carbamazepine dose is not. In addition, duration and dose of valproic acid are not associated with low total serum calcium level.